Which aging group prone to have inadequate nutrient intake?: TUA study - Nik Nur Izzati Nik Mohd Fakhruddin,; Suzana Shahar,; Nurul Atiqah Abd Aziz,; Hanis Mastura Yahya,; Roslee Rajikan, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Older adults quite often had an inadequate diet leading to micronutrient deficiencies and impaired immune response with subsequent development of degenerative diseases. This study aimed to determine the adequacy of energy and nutrient intake and its distribution among three aging groups i.e. successful aging (SA), usual aging (UA) and mild cognitive impairment (MCI). This is a cross-sectional study involving a large sample size (n = 2322) of older adults recruited through multistage random sampling from four states of Malaysia. An interview was conducted to measure dietary intake, neurocognitive status and functional status by using the Diet History Questionnaire (DHQ), Mini-Mental State Examination (MMSE), Rey Auditory Learning Test (RAVLT), Geriatric Depression Scale (GDS), Instrumental Activity of Daily Living (IADL) and Quality of Life Questionnaire. For comparison of dietary intake, a sub-sample of 173 respondents from each aging groups were matched and selected using a comparative cross-sectional approach. Women in SA group had the highest mean intake of vitamin A, calcium (p <0.05), vitamin C, riboflavin and iron (p<0.001). The same aging group also achieved the highest RNI percentage for the same nutrients. More than 80% of respondents for all aging groups did not met the recommended nutrient intake (RNI) for vitamin E, thiamin, niacin, folate, calcium and zinc. In women, MCI respondents were more likely to have an inadequate intake of vitamin A, C, riboflavin and iron followed by UA and SA. Inadequate vitamin E, niacin, folate and calcium were prevalent among all gender and aging groups. There is a need to further distinguish specific dietary patterns associated with these three aging groups to promote optimal nutrient intake for cognitive health.